1990
DOI: 10.1152/ajpheart.1990.258.1.h179
|View full text |Cite
|
Sign up to set email alerts
|

Subpressor angiotensin II infusions do not stimulate sympathetic activity in humans

Abstract: Angiotensin II (ANG II) exerts significant direct and indirect pressor and chronotropic effects in experimental animals. The indirect effects have been shown to be due to interactions with the sympathetic nervous system at several levels. To test the hypothesis that ANG II in subpressor doses enhances the activity of the sympathetic nervous system in humans either at rest or in response to a stimulus from baroreceptor unloading, we measured mean arterial pressure (MAP), heart rate (HR), plasma norepinephrine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, ANG II infusion alone had no effect on the basal output of NE from the heart (22). In human subjects, IV infusion of subpressor (15) and pressor (16) doses of ANG II does not result in increased NE spillover in plasma. In the present study, we found that infusion of pharmacological doses of ANG II into the arterial blood supply of right atrial neurons caused a threefold increase in ISF NE without spillover of NE into the coronary sinus.…”
Section: Discussionmentioning
confidence: 95%
“…However, ANG II infusion alone had no effect on the basal output of NE from the heart (22). In human subjects, IV infusion of subpressor (15) and pressor (16) doses of ANG II does not result in increased NE spillover in plasma. In the present study, we found that infusion of pharmacological doses of ANG II into the arterial blood supply of right atrial neurons caused a threefold increase in ISF NE without spillover of NE into the coronary sinus.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, in contrast to animal studies (Sanderford & Bishop, 2000, 2002), some earlier studies showed that physiological elevations of arginine vasopressin did not alter cardiac or sympathetic baroreflex function, while much higher levels of vasopressin enhanced the vasomotor sympathetic response to unloading of baroreceptors in healthy humans (Ebert & Cowley, 1992; Goldsmith, 1994). It was also found that subpressor doses of angiotensin II did not affect plasma noradrenaline (norepinephrine) concentration (Goldsmith & Hasking, 1990); however, much higher doses of angiotensin II increased muscle sympathetic nerve activity (Matsukawa et al 1991). Although humoral changes were not measured in our subjects, the data suggest that their influences on vasomotor sympathetic neural control were limited.…”
Section: Discussionmentioning
confidence: 99%
“…16 There are no signs of sympathetic overactivity during angiotensin II infusion in dogs 17 or men. 18 Taken together, these findings argue against a significant role for the central nervous system in the slow pressor responses of angiotensin II.…”
Section: Discussion Slow Responses To Angiotensin IImentioning
confidence: 99%